Morphology and viscoelastic properties of melt‐spun HDPE/hydrotalcite nanocomposite fibers. Issue 1 (22nd August 2014) - Fambri, Luca; Dabrowska, Izabela; Ferrara, Giuseppe; Pegoretti, Alessandro
Abstract : Viscoelastic properties of nanocomposite fibers of high density polyethylene (HDPE) and organically modified hydrotalcite were studied. Neat and nanofilled HDPE fibers (with nanofiller content between 0.5 and 3 wt%) were produced by melt spinning and hot‐drawing at different draw ratios up to 20. Effect of temperature on storage modulus, loss modulus, and creep compliance were compared. Rising nanofiller content and/or drawing ratio accounted for an increase in storage modulus in the glassy (i.e., below the γ transition at −100°C) as well as in the rubbery state of non‐crystalline regions. The α relaxation temperature read‐off for the maximum of the loss modulus peak ranged from 20 to 60°C being dependent on frequency, filler content and draw ratio. Sumita model was successfully applied to evaluate the effective volume fraction of the dispersed phase; maximum fraction of immobilized matrix was observed for the composite with 1 wt% of nanofiller. Creep behavior was evaluated by fitting experimental data with the Burgers model. The addition of a small amount of well‐dispersed hydrotalcite (0.5–1 wt%) had a beneficial effect on the creep resistance of drawn fibers at room temperature as well as at 70°C. TEM analysis evidenced a good dispersion of 0.5% nanofiller in as‐spun fibers and improved interfacial adhesion after drawing. The best mechanical properties were observed for the composition with 1 wt% of hydrotalcite, due to combined effects of nanofiller reinforcement and stiffening produced by hot drawing. POLYM. COMPOS., 288–298, 2016. © 2014 Society of Plastics Engineers